2006
DOI: 10.1007/s00198-006-0249-0
|View full text |Cite
|
Sign up to set email alerts
|

Bone density in relation to alcohol intake among men and women in the United States

Abstract: Drinking alcohol, but not binge drinking, appears to be beneficial to bone health of men and possibly postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 38 publications
4
32
1
Order By: Relevance
“…In our study there were no significant associations of alcohol on BMD levels in girls, supported also by Dorn et al On the contrary; in boys, alcohol consuming was significantly and positively associated to BMD at the hip sites, supported by findings in adults where moderate alcohol consumption appears to be beneficial to men´s bone health [44,45]. This effect has been suggested by Wosje and Kalkwarf to be linked to the promotion of endogenous estrogen synthesis, and thereby increasing BMD in individuals with low circulating estrogen concentrations [44].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study there were no significant associations of alcohol on BMD levels in girls, supported also by Dorn et al On the contrary; in boys, alcohol consuming was significantly and positively associated to BMD at the hip sites, supported by findings in adults where moderate alcohol consumption appears to be beneficial to men´s bone health [44,45]. This effect has been suggested by Wosje and Kalkwarf to be linked to the promotion of endogenous estrogen synthesis, and thereby increasing BMD in individuals with low circulating estrogen concentrations [44].…”
Section: Discussionsupporting
confidence: 88%
“…This effect has been suggested by Wosje and Kalkwarf to be linked to the promotion of endogenous estrogen synthesis, and thereby increasing BMD in individuals with low circulating estrogen concentrations [44]. Anyhow; this result must be interpreted carefully, as the questions about alcohol consumption has not been validated for this age group.…”
Section: Discussionmentioning
confidence: 96%
“…This was consistent with Cardiovascular Health Study, which suggested a positive relation between moderate alcohol intake and BMD at the hip among old adults aged 465 years (Mukamal et al, 2007;Tucker et al, 2009). A cross-sectional study also demonstrated that alcohol intake was linearly related to BMD at the hip and spine in old men aged 465 years (Cawthon et al, 2006) and drinking alcohol was beneficial to the bone health of men and possibly postmenopausal women (Wosje and Kalkwarf, 2007). The mechanisms for the protective effects of alcohol intake on BMD are less clear.…”
Section: Discussionsupporting
confidence: 81%
“…Although earlier observations suggested a potential protective effect of moderate alcohol consumption on BMD at the femoral neck and/or lumbar spine in postmenopausal women (10)(11)(12)(14)(15)(16)18,(20)(21)(22)(23) , highest BMD values were mostly found in women who consumed at least one drink daily. Among a group of peri-and postmenopausal women, alcohol consumption (mean intake of consumers was 125 g/week) was a positive predictor for spine BMD (3) .…”
Section: Discussionmentioning
confidence: 78%
“…Additionally, low body weight or low BMI, which are strong predictors of osteoporotic fractures (48) , frequently Table 2 Characteristics of the study participants according to alcohol intake assessed using the lifestyle questionnaire: elderly Finnish women (n 300), Kuopio Osteoporosis Risk Factor and HT, hormone therapy; BMD, bone mineral density. *The difference between categorical variables was analysed using the x occur in alcohol-drinking elderly women (12,14,16,18,20,21,25) . However, in our sample there were no statistically significant differences in BMI across the categories of alcohol intake.…”
Section: Discussionmentioning
confidence: 99%